(untitled) - Manchester, William (Boston, 1992)
From tales of chivalrous knights to the barbarity of trial by ordeal, no era has been a greater source of awe, horror, and wonder than the Middle Ages. In handsomely crafted prose, and with the grace and authority of his extraordinary gift for narrative history, William Manchester leads us from a civilization tottering on the brink of collapse to the grandeur of its rebirth-the dense explosion of energy that spawned some of history's greatest poets, philosophers, painters, adventurers, and reformers, as well as some of its most spectacular villains- the Renaissance.
Keywords: Renaissance,Learning and scholarship,Học bổng và học tập; History,Lịch sử; Medieval, 500-1500,Thời cổ đại, 500-1500